Induction of potent antitumor CTL responses by recombinant vaccinia encoding a melan-A peptide analogue. - Valmori, D; Lévy, F; Miconnet, I; Zajac, P; Spagnoli, G; Rimoldi, D; Liénard, D; Cerundolo, V; Cerottini, J; Romero, P (2000)
There is considerable interest in the development of vaccination strategies that would elicit strong tumor-specific CTL responses in cancer patients. One strategy consists of using recombinant viruses encoding amino acid sequences corresponding to natural CTL-defined peptide from tumor Ags as immunogens. However, studies with synthetic tumor antigenic peptides have demonstrated that introduction of single amino acid substitutions may dramatically increase their immunogenicity. In this study we have used a well-defined human melanoma tumor Ag system to test the possibility of translating the immunological potency of synthetic tumor antigenic peptide analogues into recombinant vaccinia viruses carrying constructs with the appropriate nucleotide substitutions. Our results indicate that the use of a mutated minigene construct directing the expression of a modified melanoma tumor Ag leads to improved Ag recognition and, more importantly, to enhanced immunogenicity. Thus, recombinant vaccinia viruses containing mutated minigene sequences may lead to new strategies for the induction of strong tumor-specific CTL responses in cancer patients.